Encryption using FPGA - Nor Robaini, Ibrahim (2008)
Advanced Encryption Standard (AES), a Federal Information Processing Standard (FIPS), is an approved cryptographic algorithm that can be used to protect electronic data. The AES algorithm is a block cipher that can encrypt and decrypt digital information. The AES algorithm is capable of using cryptographic keys of 128, 192, and 256 bits, this project implements the 128 bit standard on a Field Programming Gate Array (FPGA) using the VHDL, a hardware description language.